2016
DOI: 10.5505/phd.2016.82905
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Assessment Scale of Adaptation Difficulty for the Elderly (ASADE) and Its Psychometric Properties

Abstract: The aim of this study was to develop the Assessment Scale of Adaptation Difficulty for the Elderly and determine its reliability and validity. Methods:The study sample was comprised of 309 elderly participants aged 65 and older living in 2 nursing homes. The theoretical framework for the scale was the Roy Adaptation Model. The construct validity of the scale was tested using exploratory factor analysis, and reliability was assessed using internal consistency and split-half reliability. Results:The content vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 5 publications
(11 reference statements)
1
24
0
Order By: Relevance
“…However, needs may be inadequately met when individuals move to live in a nursing home, and they can develop adaptation difficulties as well as feelings of depression, anxiety, weakness and reduced self-worth. 6,18 In the present research, most participants had good overall adaptation and could still do their daily work independently (80.6%). However, adaptations to changed roles and self-actualisation were more negative compared with that in other dimensions, similar to previous reports.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…However, needs may be inadequately met when individuals move to live in a nursing home, and they can develop adaptation difficulties as well as feelings of depression, anxiety, weakness and reduced self-worth. 6,18 In the present research, most participants had good overall adaptation and could still do their daily work independently (80.6%). However, adaptations to changed roles and self-actualisation were more negative compared with that in other dimensions, similar to previous reports.…”
Section: Discussionmentioning
confidence: 53%
“…The fundamental requirement of role and self-actualisation is arguably social integration, and another study reported that the weakening of social relations and detachment from society increased the risk of cognitive decline in the elderly and were significantly associated with death. 18,22 This finding of our study is important for determining the changing roles that emerge due to aging.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations